Modern approaches to selecting testing means and assessment of students’ performance (Journal of Educational Sciences, 2021)
The article provides a detailed description of modernization of learning results assessment system in the context of important directions of education quality assurance in higher educational establishment. The article is of an overview nature. The main focus is on the demands to teachers’ competences in as- sessing students. Assessment competence of a lecturer is a voluminous concept associated with modern concepts of pedagogical and psychological measurement, possession of design and assessment tools, the organization of the assessment process by a teacher, and self-assessment and mutual assessment of students. It also reveals the features of assessing the success of students, the systematic nature of the control and the role of the teacher in this process. The research also reveals peculiarities of assessing students’ performance, systematic character of testing and defines the role of a teacher in this process. The article reveals two approaches to assessing the educational achievements of an individual according to educational standards: (1) assessing the minimum level of educational achievement or the minimum required competence; (2) division of educational achievements into several levels of competence.The article gives information on the peculiarities of testing development, its theoretical approaches, main terms, notions and indicators of quality, represents the stages of test creation. Research has shown that there has been an overwhelming focus on written and computer-based testing lately. Special atten- tion is paid to the aspects of applying test tasks to improve the quality of education in higher educational establishment.Key words: assessment, assessing students’ performance, monitoring, testology, testing, pedagogi- cal task, a test, computer system of testing.